Taboo Words in Manggaraian Language: Socio-Pragmatic Analysis - Gunas, Tobias (International Seminar on Austronesian Languages and Literature, 2021)
Taboo words are generally recognized and spoken by speakers of any language in communication. However, taboo words richly vary in form, meaning, and use in societies in different languages. As with the case of taboo words, Manggaraian language employs some specific lexicons having different forms, meaning, reference and use among its speakers.  This research aims to explore taboo words in the Manggaraian language from the socio-pragmatic analysis. The descriptive qualitative research method was applied to account for taboo words in the Manggaraian language, whereas the primary data were naturally obtained through field observation, recording, and interview. The data were descriptively analyzed through three procedures, namely: reduction, display, and conclusion drawing. The data analysis is, furthermore, based on the theories of taboo language and socio-pragmatics. The results of the study reveal that taboo words in the Manggaraian language are generally classified into profanity, obscenity, epithet, and scatology. These types of taboo words serve some functions such as expressing feeling/emotion, cursing, swearing, closeness and humor, group identity/ethnicity, and drawing attention. The matters of the taboo words refer to sex, physical appearance, animal, waste, and metaphysical things.  Socio-pragmatically, the use of taboo words is considered to be a deviant behavior of social norms and impolite words for Manggaraian speakers in daily communication. Taboo words are determined by socio-cultural aspects and contexts of communication .